The technology of identification, interpretation and mapping of degraded lands based on remote sensing data - Alsheuski, Aleksey V.; Samsonenka, Igor P.; Yatsukhna, Valentin M. (Journal of the Belarusian State University. Geography and Geology, 2019)
Described experimental sample of the technology of identification, interpretation and mapping of degraded land, created in the framework of the Union State program «Monitoring-SG». The experimental sample is based on the use of GIS models of automatization of remote sensing data (RSD) processing, created on the basis of an open geoinformation software QGIS. Developed GIS models are used together to implement an automated pre-processing, satellite images classification, accuracy assessment of the classification and vectorization and mapping of the received results of thematic interpretation. The proposed technology allows to create digital land degradation maps, provides a cost savings and simplification of remote sensing data processing. The database of degraded lands and the electronic atlas of land degradation forms of the Republic of Belarus are created, access to which is realized through a dedicated geoportal (web-service). The research results could be applied for combat land degradation at national level, but also at the solution of tasks of creating and updating of cartographic products, development of thematic geographic information systems and land use planning documents.